Cell-based glycan arrays for probing glycan–glycan binding protein interactions - Jennie Grace Briard; Hao Jiang; Kelley W. Moremen; Matthew Scott Macauley; Peng Wu (Nature Communications, 2018)
Glycans, interaction platforms protruding from the surface of cells, are hard to study due to their diverse architecture. Here, the authors present a method to obtain cells carrying defined glycans, which can then be used to find proteins specifically recognizing these tags.